Non-european Auchenorrhyncha (Hemiptera) and their geographical distribution in Slovenia - Seljak, Gabrijel (Acta entomologica slovenica (Ljubljana), 2002)
Four non-European species of Auchenorrhyncha have spread into Slovenia in the last 40 years: Metcalfa pruinosa, Stictocephala bisonia, Scaphoideus titanus and Japananus hyalinus. Their current distribution in Slovenia and the consequences of their appearance are discussed in brief.
Keywords: Hemiptera; prevalence; razširjenost; Slovenia; Slovenija; škržati